Rozwiąż równania
a) x+2 = 1/2
b) x-3=4 1/2
c) x+1/2=6
d) 1-x=1 1/2
e) 1/2 - x=5
f) 1 1/2 - x= - 2 1/2​



Odpowiedź :

Odpowiedź:

a) x+2=0,5 I -2

x=-1,5

b) x-3=4,5 I+3

x=7,5

c) x+0,5=6 I -0,5

x=5,5

d) 1-x=1,5 I -1

-x=0,5 I *-1

x=-0,5

e) 0,5-x=5 I -0,5

-x=4,5 I *-1

x=-4,5

f) 1,5-x=-2,5 I -1,5

-x=-4 I *-1

x=4

Odpowiedź:

a) x+2 = 1/2

x+2 = 1/2 l -2

x=-1 ½

b) x-3=4 1/2

x-3=4 1/2 l+3

x=4½+3

x=7½

c) x+1/2=6

x+1/2=6 l-½

x=5½

d) 1-x=1 1/2

1-x=1 1/2 l-1

-x= ½ l*-1

x= -½

e) 1/2 - x=5

1/2 - x=5 l-½

-x=4½ l*-1

x=-4½

f) 1 1/2 - x= - 2 1/2

1 1/2 - x= - 2 1/2l-1 ½

-x=-4 l*-1

x=4